The Effect of Bibliotherapy on Teenagers' HIV/AIDS Knowledge in the Puger Work Area Community-Based Health Centers, Jember Regency - Dini Kurniawati; Iis Rahmawati; Wan Sandra Clarista (Journal of Nursing Science Update (JNSU), 2022)
AIDS (Acquired Immune Deficiency Syndrome) is a disease caused by HIV that can lower a person's immune status to trigger an opportunistic infection and cause death. HIV / AIDS can infect all age groups, including teenagers. Bibliotherapy is a learning model to change teenagers' knowledge of HIV / AIDS. We aimed to analyze bibliotherapy's effect on teenagers' knowledge of HIV / AIDS. We used quasi-experimental research with a nonequivalent control group design approach. The population in this study was 30 teenagers, with the technique of determining the sample using purposive sampling. The research instrument used is a knowledge questionnaire. Data analysis using the Wilcoxon test and Mann-Whitney test. The analysis result showed significant differences between the pretest and post-test in the intervention group (p-value= 0.001) and control group (p-value= 0.044). Bivariate test used Mann Whitney indicating an effect of the bibliotherapy method on teenagers’ knowledge about HIV / AIDS (p-value = 0.002; p <0.05). The effect of bibliotherapy is to interpret words, sentences, and even images that are captured by the sense of sight and will be conveyed to the brain by optical chiasm when someone reads information. Therefore, the conclusion is bibliotherapy method has an effect on the knowledge of teenagers about HIV/AIDS. Nurses' role in applying bibliotherapy is to increase teenagers' knowledge to reduce the risk of HIV/AIDS in the community.